Molecular Hazard Identification of Non-O157 Shiga Toxin-Producing Escherichia coli (STEC) - Franz, Eelco (PLoS One, 2015)
The complexity regarding Shiga toxin-producing Escherichia coli (STEC) in food safety enforcement as well as clinical care primarily relates to the current inability of an accurate risk assessment of individual strains due to the large variety in serotype and genetic content associated with (severe) disease. In order to classify the clinical and/or epidemic potential of a STEC isolate at an early stage it is crucial to identify virulence characteristics of putative pathogens from genomic information, which is referred to as ‘predictive hazard identification’. This study aimed at identifying associations between virulence factors, phylogenetic groups, isolation sources and seropathotypes. Most non-O157 STEC in the Netherlands belong to phylogroup B1 and are characterized by the presence of ehxA, iha and stx (2), but absence of eae. The large variability in the number of virulence factors present among serogroups and seropathotypes demonstrated that this was merely indicative for the virulence potential. While all the virulence gene associations have been worked out, it appeared that there is no specific pattern that would unambiguously enable hazard identification for an STEC strain. However, the strong correlations between virulence factors indicate that these arrays are not a random collection but are rather specific sets. Especially the presence of eae was strongly correlated to the presence of many of the other virulence genes, including all non-LEE encoded effectors. Different stx-subtypes were associated with different virulence profiles. The factors ehxA and ureC were significantly associated with HUS-associated strains (HAS) and not correlated to the presence of eae. This indicates their candidacy as important pathogenicity markers next to eae and stx (2a).